Nietzsche e a modernidade: da crítica à metafísica à crítica à democracia - Vieira, Mauro Rogério de Almeida (2012)
This dissertation presents an interpretation concerning the critical considerations of the German philosopher Friedrich Nietzsche on Modernity, especially Nietzsche s criticism of Modernity, of Christian mores and democracy produced by him in Beyond Good and Evil. Nietzsche attentively analyses details of Modernity, produces a diagnosis of modern man and discovers the sign of decay. We consider that Nietzsche s criticism of modernity is directly linked to the criticism of classic metaphysics. We emphasize questions like: what in us aspires to truth? Christian mores: why and what for? What characterizes modernity? Could it be the appeal to the democratic taste? Is it possible to reinvent Modernity? We stress the relation between the notion of truth, democracy and Christian mores, showing that these mores were also inherited from the Socratic culture. We also intend to clarify Nietzsche s proposal of a new way of doing philosophy, that would be able to surpass the decay which rules in European modern culture. The end of this research points out to the ―philosophers of the future‖ who are able, according to Nietzsche, to claim life beyond the metaphysics opposition, beyond the good and the evil